Path-sampling strategies for simulating rare events in biomolecular systems. (April 2017) - Chong, Lillian T; Saglam, Ali S; Zuckerman, Daniel M
Highlights: Advances, common features, and remaining challenges are presented for path sampling approaches. Key strengths are the efficient calculation of transition trajectories and rate constants. Successful applications include protein conformational changes, (un)folding and (un)binding. Abstract : Despite more than three decades of effort with molecular dynamics simulations, long-timescale (ms and beyond) biologically relevant phenomena remain out of reach in most systems of interest. This is largely because important transitions, such as conformational changes and (un)binding events, tend to be rare for conventional simulations (<10 μs). That is, conventional simulations will predominantly dwell in metastable states instead of making large transitions in complex biomolecular energy landscapes. In contrast, path sampling approaches focus computing effort specifically on transitions of interest. Such approaches have been in use for nearly 20 years in biomolecular systems and enabled the generation of pathways and calculation of rate constants for ms processes, including large protein conformational changes, protein folding, and protein (un)binding.